Real-time Adherence Monitoring of Antiretroviral Therapy Among HIV-infected Adults and Children in Rural Uganda - Haberer, Jessica E.; Kiwanuka, Julius; Nansera, Denis; Muzoora, Conrad; Hunt, Peter W.; Jacquelyn, So; O'Donnell, Michael; Siedner, Mark; Martin, Jeffrey N.; Bangsberg, David R. (AIDS, 2013)
A real-time wireless electronic adherence monitor(EAM) and weekly self-report of missed doses via interactive voice response (IVR) and short message service (SMS) queries were used to measure ART adherence in 49 adults and 46 children in rural Uganda. Median adherence was 89.5% among adults and 92.8% among children by EAM, and 99–100% for both adults and children by IVR/SMS self-report. Loss of viral suppression was significantly associated with adherence by EAM (OR 0.58 for each 10% increase), but not IVR/SMS. Wireless EAM creates an exciting opportunity to monitor and potentially intervene with adherence challenges as they are happening.